Ventricular septal defect after myocardial infarction: assessment by cross sectional echocardiography with pulsed wave Doppler scanning. Issue 3 (September 1987) - MacLeod, D; Fananapazir, L; de Bono, D; Bloomfield, P
Abstract : Eight patients who developed a ventricular septal defect after myocardial infarction were assessed by cross sectional echocardiography and pulsed wave Doppler scanning. Cross sectional echocardiography visualised the defect in four patients and gave an accurate assessment of global and regional left ventricular function in all eight. In all patients pulsed wave Doppler scanning detected turbulent flow at the apex of the right ventricle or adjacent to a wall motion abnormality affecting the interventricular septum. Pulsed wave Doppler detected coexisting mitral regurgitation in one patient and tricuspid regurgitation in another two. In all patients a left to right shunt was confirmed by oximetry and the location of the defect was identified by angiography or at operation or necropsy. Cross sectional echocardiography in combination with pulsed wave Doppler scanning is useful in the rapid bedside evaluation of patients with ventricular septal defect after myocardial infarction.